Diurnal Variation in Medical Emergency Team Calls at a Tertiary Care Children’s Hospital - Conway, Susan R. (Pediatr Qual Saf, 2020)
Medical emergency teams (METs) bring critical care expertise to the bedsides of hospital ward patients who may be deteriorating. Diurnal variation in MET activation rates may identify inconsistencies in the detection of patients needing intervention. We aimed to determine whether such variation exists at our tertiary care children’s hospital. METHODS: In this retrospective cohort study, we collected data including date and time of MET and disposition following MET for all inpatients at Cincinnati Children’s Hospital Medical Center with a MET call between January 2008 and May 2014. The analysis compared the MET rate between days and nights, weekdays and weekends, and before and after nursing shift change. RESULTS: The number of METs per hour varied throughout the day. More METs were called during the day than at night (0.7 calls/shift ± 0.95 vs 0.6 ± 0.9, P < 0.001). There were also more METs per day on weekdays than weekends (1.4 ± 1 calls/d vs 1.2 ± 1, P < 0.001). Daytime METs were more likely to lead to transfer to the intensive care unit or operating room than those called at night (61.9% vs. 52.9%, P < 0.001). MET activation rates did not differ significantly in the 2 hours before nursing shift change compared to the 2 hours after. CONCLUSIONS: At our large tertiary care children’s hospital, there are both diurnal variations and variations across weekdays versus weekends in the MET activation rate. This difference may indicate variations in our ability to detect deteriorating patients on the wards and be further studied.